Nano-fluid loss agent based on an acrylamide based copolymer "grafted" on a modified silica surface. Issue 21 (9th February 2016) - An, Yuxiu; Jiang, Guancheng; Qi, Yourong; Ge, Qingying; Zhang, Lingyu
Abstract : In this paper, the nano copolymer of acrylamide (AM), 2-acrylamido-2-methyl-1-propane sulfonic acid (AMPS), and modified nano-silica (M-SiO2 ) was synthesized by free radical polymerization in a water solution. Abstract : In this paper, the nano copolymer of acrylamide (AM), 2-acrylamido-2-methyl-1-propane sulfonic acid (AMPS), and modified nano-silica (M-SiO2 ) was synthesized by free radical polymerization in a water solution. The addition of ethanol was used to control the molecular weight of the copolymer. The characterization of the copolymer was measured by Fourier transform infrared spectroscopy, a particle size analyzer, transmission electron microscopy, atomic force microscopy and nuclear magnetic resonance. AM and AMPS were grafted on the surface of M-SiO2 successfully. The grafted copolymer was in nm size not only in the water solution but also in a drilling fluid. Filtration properties and the interaction mechanism of the copolymer with montrillonite (MMT) were studied in a fresh water drilling fluid system and different kinds of salt water drilling fluid systems. The copolymer as fluid loss agent was equal to commonly used fluid loss agents in a fresh water drilling fluid system. The resistance properties to salinity, calcium and high temperature were tested. The copolymer had a resistance temperature of 150 °C and saturated brine resistance. The resistance property to calcium was up to 1 wt%. The interaction mechanism between montrillonite and the copolymer was evaluated using a particle size analyzer, transmission electron microscopy, scanning electron microscopy and a surface area analyzer. The copolymer was adsorbed on the surface of MMT. Compared to pristine MMT, the addition of the copolymer resulted in new peaks in the particle size analyzer image. The filter liquor of the drilling fluid with the copolymer showed two peaks in nm scale and the filter liquor of the drilling fluid without the copolymer showed that no peak appeared under 1000 nm. The results presented that the copolymer as a fluid loss agent was a nano material in the drilling fluid. The surface area analyzer (BET) results showed that the surface area of a natural rock reduced after treatment with the copolymer, indicating that the copolymer entered into the nanopores of shale because of the adsorption on the surface of shale.